In Barbary Tunisia, Algeria, Morocco, and the Sahara - Powell, E. Alexander (Edward Alexander), 1879-1957 (Century Co., 1926)
Presents narratives of the author's adventures and travels in North Africa in late 19th century and early 20th century.